Analysis of #banksyariah posts through social media marketing: as a means of sharia product knowledge - Risza, Handi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
The banking industry, especially Sharia banks, continues strengthening marketing communications and consumer education regarding Sharia-related information through social media marketing. Information dissemination by Islamic banks is important because it can encourage additional information and influence other consumers. This information can be in the form of the latest news, marketing programs, policies, or education to consumers to strengthen consumer product knowledge. This study identifies the use of social media as the leading platform to find out the conversations that are carried out by the public on social media related to the differences between Islamic and conventional banking; conversations conducted by consumers on social media related to products or contracts owned by Islamic banking and conversations conducted by the public on social media related to knowledge (literacy) and selection of Islamic banking products (inclusion).